2003
DOI: 10.1079/phn2002355
|View full text |Cite
|
Sign up to set email alerts
|

Increased intake of fruit and vegetables: estimation of impact in terms of life expectancy and healthcare costs†

Abstract: Objectives: There is strong evidence that a high consumption of fruit and vegetables reduces the risk of developing many cancers. This study examined the economic consequences for the healthcare sector if people followed the recommendations and increased their intake of fruit and vegetables. Design: A life table was used to describe a base case population with respect to life expectancy, cancer incidence and healthcare costs. Relative risks of cancer for a high versus a low intake of fruit and vegetables were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 9 publications
0
61
0
1
Order By: Relevance
“…Given that the limited resources of IHS are used mostly for treatment and that treatment costs are high, a far more cost-effective strategy would be to focus efforts on nutritional intervention programmes for prevention of obesity, diabetes and chronic diseases in this high-risk population. Substantial evidence suggests that improving diet and nutrition could reduce the risk of diabetes, cancer and CVD, which would result in decreasing the incidence, mortality and economic cost of these chronic diseases (11)(12)(13)(14)(15)(16)(17)(18) . The Navajo Healthy Store (NHS) intervention programme was designed to improve dietary quality and reduce risk for obesity by increasing the availability, purchase and consumption of healthy foods for the Navajo Nation.…”
mentioning
confidence: 99%
“…Given that the limited resources of IHS are used mostly for treatment and that treatment costs are high, a far more cost-effective strategy would be to focus efforts on nutritional intervention programmes for prevention of obesity, diabetes and chronic diseases in this high-risk population. Substantial evidence suggests that improving diet and nutrition could reduce the risk of diabetes, cancer and CVD, which would result in decreasing the incidence, mortality and economic cost of these chronic diseases (11)(12)(13)(14)(15)(16)(17)(18) . The Navajo Healthy Store (NHS) intervention programme was designed to improve dietary quality and reduce risk for obesity by increasing the availability, purchase and consumption of healthy foods for the Navajo Nation.…”
mentioning
confidence: 99%
“…Firstly, the universal use of the unique personal identification number, rendering register linkages straightforward and easy, allow us to follow individuals and their healthcare use over time and between institutions; as well as linking these data with other data of relevance for a specific study like income or geographical area of residence. The majority of the assessed studies have selected a group of individuals in a cohort [7,8,10], a patient register [3,13], or from a randomised study [4À6], and subsequently identified these in the national registers by means of register linkages.…”
Section: Resultsmentioning
confidence: 99%
“…In an economic evaluation of the beneficial effect of fruit and vegetables consumption on cancer incidence [3], Gundgaard et al used the Danish National Patient Register and the Danish National Health Service Register to compute the attributable costs of cancer incidence, by comparing healthcare costs for cancer patients to healthcare costs for people that were not cancer patients. The authors used the Danish Cancer Registry for identification of cancer patients.…”
Section: Use Of Register-based Data For Cost Assessments In Economic mentioning
confidence: 99%
“…Several epidemiological studies have indicated that a high intake of plant products is associated with a reduced risk of some chronic diseases, such as atherosclerosis and cancer (Gosslau and Chen 2004, Gundgaard et al 2003, Linnewiel et al 2015. These beneficial effects have been partly attributed to compounds with antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%